Analysis of User Acceptance of the Access by KAI Online Ticket Booking Application using TAM - Prameswari Fayra Mutia; Apriansyah Putra (SISTEMASI, 2026)
Information technology (IT) has transformed ticketing systems in public transportation and other service industries. The Access by KAI online application, developed by PT Kereta Api Indonesia (Persero), facilitates train ticket purchases. This application features electronic boarding, travel itinerary information, and ticket booking services, thereby streamlining the user’s travel experience. However, users still raise concerns regarding the usability of the application. This study employs the Technology Acceptance Model (TAM) framework to assess user acceptance of the Access by KAI application. This quantitative study collected data from Access by KAI users through a questionnaire survey. Actual System Use (ASU) serves as the dependent variable, while Perceived Ease of Use (PEOU), Perceived Usefulness (PU), Attitude Toward Use (ATU), and Behavioral Intention (BI) function as independent and mediating variables. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS software. The results show that four out of five hypotheses are supported, while one is not. The analysis indicates that Perceived Usefulness and Perceived Ease of Use significantly influence Attitude Toward Use and Perceived Usefulness. Another important finding is that Behavioral Intention and Attitude Toward Use have a strong influence on Actual System Use. However, the model does not demonstrate a significant effect for one of the hypothesized relationships. Overall, the findings suggest that users’ attitudes and intentions toward using the Access by KAI application are influenced by their perceptions of its ease of use and the benefits it provides. This study is expected to provide PT Kereta Api Indonesia (Persero) with evaluative insights to enhance service quality, improve user acceptance, and increase the usability of the Access by KAI application.